Visualization of dental plaque with a 3D-intraoral-scanner-A tool for whole mouth planimetry. - Katja Jung; Katja Giese-Kraft; Melanie Fischer; Kai Schulze; Nadine Schlueter; Carolina Ganss (PLoS ONE)
Planimetry is a reliable method for detecting and monitoring plaque. Until now, this method has mainly been applied to conventional-camera images, which is difficult and time-consuming in relation to the entire dentition. Today, 3D-intraoral-scans are well suited for imaging the entire dentition and are therefore an efficient and feasible alternative. 3D-intraoral-scans have already proven successful for the quantification of plaque based on a plaque index. Therefore, aim of this study was to investigate whether images from 3D-intraoral-scans are also suitable for valid planimetric plaque measurements and monitoring; intraoral-camera images served as a reference. Twenty subjects (27.5±1.2 years) were included. Plaque was disclosed at three different time points: habitual plaque (T1), after 72 h without oral hygiene (T2) and after subsequent tooth brushing (T3) and quantified using 3D-intraoral-scans and intraoral-camera images (intraoral-camera CS 1500, intraoral-scanner CS 3600; Carestream Dental, Germany). The percentage of the plaque-covered surface of the total surface area (P%) was determined with a software specially programmed for this purpose using images from 3D-intraoral-scans of the oral and vestibular surfaces of the Ramfjord teeth (16, 21, 24, 36, 41, and 44); the intraoral-camera images of the vestibular surfaces of 16 and 36 served as reference. P% from images of the 3D-intraoral-scan and the intraoral-camera revealed a very good correlation (r = 0.876; p ≤ 0.001); the Bland-Altmann analysis showed a good agreement with no proportional and a very minor systematic bias with slightly higher values from images of the 3D-intraoral-scan. Further, P% measurements of the images of the 3D-intraoral-scan were able to detect changes in plaque levels, showing a 47% (p ≤ 0.001) increase in P% from T1 to T2 and a 43% (p ≤ 0.001) decrease after toothbrushing (T3). Planimetry using images of the 3D-intraoral-scan seems to be a suitable tool for whole mouth planimetry to record and monitor dental plaque.